2017
DOI: 10.1165/rcmb.2016-0380oc
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Wildfire Smoke Exposure Is Associated with Immune Dysregulation and Lung Function Decrements in Adolescence

Abstract: The long-term health effects of wildfire smoke exposure in pediatric populations are not known. The objectives of this study were to determine if early life exposure to wildfire smoke can affect parameters of immunity and airway physiology that are detectable with maturity. We studied a mixed-sex cohort of rhesus macaque monkeys that were exposed as infants to ambient wood smoke from a series of Northern California wildfires in the summer of 2008. Peripheral blood mononuclear cells (PBMCs) and pulmonary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 43 publications
6
73
1
Order By: Relevance
“…The only comparable study, in terms of exposure, was conducted in monkeys but not in humans. The California fires of 2008 caused degraded air quality for a period of 3 weeks in a primate research facility soon after the birth of 50 rhesus macaque monkeys, and their lung function was evaluated in adolescence . Unlike our results, these authors found moderate reductions in airway resistance in the exposed animals compared with the unexposed indicating better lung function.…”
Section: Discussioncontrasting
confidence: 96%
“…The only comparable study, in terms of exposure, was conducted in monkeys but not in humans. The California fires of 2008 caused degraded air quality for a period of 3 weeks in a primate research facility soon after the birth of 50 rhesus macaque monkeys, and their lung function was evaluated in adolescence . Unlike our results, these authors found moderate reductions in airway resistance in the exposed animals compared with the unexposed indicating better lung function.…”
Section: Discussioncontrasting
confidence: 96%
“…Animal models of lung development suggest a strong oxidant exposure in early life changes lung function by altering the pattern and timing of alveolarization and distal airway development (Avdalovic et al, 2012; Fanucchi et al, 2006). This is consistent with animal studies showing altered lung volumes in nonhuman primates exposed to wildfire smoke during infancy (Black et al, 2017). A mechanism explaining the health effects of wildfire smoke would help to predict how wildfire smoke interacts with the developing lung and other long-term health considerations in specific populations.…”
Section: Discussionsupporting
confidence: 91%
“…A study of these animals performed 3 years later (as juveniles) found that compared to age-matched peers, these animals had reduced lung volumes. Furthermore, stimulation of peripheral blood mononuclear cells collected from the animals produced lower levels of inflammatory cytokines in response to Toll-like receptor ligands compared to age-matched controls that were not exposed to wildfire smoke as infants (Black et al, 2017). …”
Section: Health Effects Of Wildfire Smokementioning
confidence: 99%
“…We focus on children given their reduced lung size, increased metabolic rates, higher respiratory rate, and developing immune systems, 5 and because in macaque monkeys who are exposed to wildfire smoke in infancy, there is associated immune dysregulation and decreased lung function in adolescence. 6 We hypothesize that the health impacts of a prescribed fire are less detrimental to the respiratory and cardiovascular systems than a wildfire in school-aged children and…”
Section: To the Editormentioning
confidence: 99%